2022
DOI: 10.1098/rspb.2022.0348
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among multiple stressors vary with exposure duration and biological response

Abstract: Coastal ecosystems are exposed to multiple anthropogenic stressors. Effective management actions would be better informed from generalized predictions of the individual, combined and interactive effects of multiple stressors; however, few generalities are shared across different meta-analyses. Using an experimental study, we present an approach for analysing regression-based designs with generalized additive models that allowed us to capture nonlinear effects of exposure duration and stressor intensity and acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 63 publications
4
17
0
Order By: Relevance
“…The interaction between light and herbicide at the highest stressor intensities for biomass leans towards an antagonism when introduced in‐ and out‐of‐phase. High bias statistics for both in‐and out‐of‐phase treatments also suggested the potential for stronger stressor interactions at higher intensities, a finding consistent with previous theoretical predictions and empirical experiments (King et al, 2022 ; Turschwell et al, 2022 ). For example, a stronger synergistic effect of reduced light and herbicide contamination on algal growth inhibition was observed at the highest stressor intensities (King et al, 2022 ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The interaction between light and herbicide at the highest stressor intensities for biomass leans towards an antagonism when introduced in‐ and out‐of‐phase. High bias statistics for both in‐and out‐of‐phase treatments also suggested the potential for stronger stressor interactions at higher intensities, a finding consistent with previous theoretical predictions and empirical experiments (King et al, 2022 ; Turschwell et al, 2022 ). For example, a stronger synergistic effect of reduced light and herbicide contamination on algal growth inhibition was observed at the highest stressor intensities (King et al, 2022 ).…”
Section: Discussionsupporting
confidence: 86%
“…High bias statistics for both in‐and out‐of‐phase treatments also suggested the potential for stronger stressor interactions at higher intensities, a finding consistent with previous theoretical predictions and empirical experiments (King et al, 2022 ; Turschwell et al, 2022 ). For example, a stronger synergistic effect of reduced light and herbicide contamination on algal growth inhibition was observed at the highest stressor intensities (King et al, 2022 ). Therefore, we suggest that extreme synergisms and antagonisms can occur at higher stressor intensities, amplifying or reducing the impacts of in‐ and out‐of‐phase fluctuations than those hypothesised in our conceptual model.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Since two community metrics can observe opposite interactions between the same stressors, it is unwise to think of stressor interactions at the community level as “intrinsic” to the stressors themselves. As there is growing interest in the existence of context dependency of stressor interactions (Turschwell et al, 2022; King et al, 2022), development of general theory is sorely needed. Our work offers a mechanistic explanation for one of the drivers of this context dependency: observations at the community level.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it was also found that rapid evolution can create novel synergisms between multiple drivers ( Orr et al, 2022 ). Besides evolutionary processes, phenotypic plasticity may influence the response to multiple drivers over shorter time scales and hence the duration of the exposure is an important consideration ( King et al, 2022 ). However, given that both evolution and phenotypic plasticity will shape the reaction norms of vital rates, our approach readily allows us to account for these processes occurring over time.…”
Section: Implications For Future Research and Conclusionmentioning
confidence: 99%